Evaluation of the Functionality of Mineral-Resin Pavement - Łukasz Bednarek; Nadzeya Fialkouskaya (The Baltic Journal of Road and Bridge Engineering)
Due to climate change and the recent increase in the number of floods in urbanized areas, there is a growing need for the introduction of new technologies into the road material market. One such technology is water- permeable mineral-resin surfaces, which are becoming increasingly popular. However, due to a lack of clear requirements and solution approval procedures, they are not commonly used in public investments. This paper first describes the materials used for preparing surface samples, including bulk density and granulometric aggregate tests, consistency, colour, and density at 20 °C testing of the hardener and resin. It then outlines the process of sample preparation and provides a brief description of the materials used. The tests conducted on the prepared material samples included flexural and compressive strength tests, frost resistance tests under normal conditions and in the presence of salts, and skid resistance tests. Based on the results obtained, it can be generally concluded that, in the case of permeable surfaces, the type of aggregate is an important factor, as evidenced by the results of the strength tests. The same can be stated about the influence of atmospheric factors. Tests conducted with granite aggregate proved to be more resistant to cyclically changing temperatures, even in the presence of salt.